Primary Productivity of Phytoplankton of Mahakali River, Nepal - Mahasetha, Vinod Kumar (BIBECHANA, 2016)
Present paper describes primary productivity of Mahakali river at four stations. The two years mean of net primary production was 96.80 mgC/m3/day. The net primary production value of Mahakali river was less due to the low water temperature and less phytoplanktonic growth. Two years mean value of gross primary production of Mahakali river was 176.29 mgC/m3/day, which is less than lentic water. It shows that the river is oligotrophic but developing a tendency as going towards mesotrophic. BIBECHANA 14 (2017) 98-102